MEDICOSURGICAL MANAGEMENT OF SHARP CUT INJURIES OF FLEXOR TENDONS IN HARROWING BULLOCKS - Jana, Debasis; Ghosh (Jana) , Mousumi (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Cut injuries of either superficial or deep flexor tendon or both, are frequently encountered in working bullocks employed for agricultural operation during cultivation of cash crops where harrowing blades cause field accidents leading to the crippling condition of the victim putting farmers in problem during the peak preparatory phase of cultivation. In the field accidents invariably the flexor tendons get the trauma or cut injuries either partially severed or completely cut with wide gap due to which the working capacity of the bullocks are markedly impaired depending on the degree of trauma and intensity of the cut injuries to the flexor tendons. Farmers being hopeless are forced to sell their valuable bullocks to the local butchers at the cheapest rate owing to their ignorance about its correction by surgical intervention. Conventional treatment does not yield satisfactory improvement to such accident that met with causing upward movement of the hoof and incapable of weight bearing on the affected limb in question with fet lock touching on the ground. Inspite of treatment some animals are found to develop sepsis (Meshram et al. 2006). Present communication reports successful medico-surgical management of complete sharp cut injuries of flexor tendons of three bullocks that restored working capacity.